Brominated and chlorinated contaminants in food (PCDD/Fs, PCBs, PBDD/Fs PBDEs): Simultaneous determination and occurrence in Italian produce. (February 2022) - Ceci, Roberta; Diletti, Gianfranco; Bellocci, Mirella; Chiumiento, Francesco; D'Antonio, Silvia; De Benedictis, Alfonso; Leva, Manuela; Pirito, Luigi; Scortichini, Giampiero; Fernandes, Alwyn R.
Abstract: Validated methodology for the simultaneous determination of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), polybrominated dibenzo- p -dioxins and dibenzofurans (PBDD/Fs) and polybrominated diphenyl ethers (PBDEs) in foods of animal origin is presented. Method performance indicators were equivalent or better than those required for the control of EU regulated (EU, 2017/644) PCDD/F and PCB congeners in these foods, and for risk assessment through dietary intake. The method uses a high (>90%) proportion of 13 Carbon-labelled surrogates for internal standardisation combined with high resolution mass spectrometry that allow accurate quantitation, and this was confirmed by multiple successful participations in proficiency testing for PCDD/Fs, PCBs and PBDEs in food. The same validation and method performance requirements as used for PCDD/Fs were followed for PBDD/Fs. The analysis of a range of food samples (eggs, milk, fish, shellfish, pork, beef and poultry), showed the occurrence of all four classes of contaminants at varying concentration ranges. In general, PCBs were the most prominent contaminant, both, in terms of dioxin-like toxicity, as well as in the occurrence of non-dioxin-like congeners, an observation that concurs with those made in other studies on Italian foods. The levels of PCDD/F and PCB occurrence are consistent with a gradual decline in contamination as reported by some other similar studies. Although all the determined contaminants were detected in the sampled foods, there was poor correlation between the occurrences of the brominated and chlorinated contaminants, and between PBDEs and PBDD/Fs, but better associations were observed between the occurrences of the chlorinated contaminants. Highlights: Simultaneous, validated determination of PCDD/Fs, PCBs, PBDEs & PBDD/Fs in food. PCB TEQ was greater than PCDD/F or PBDD/F TEQ, in most marine/animal products. No correlation was seen between chlorinated and brominated contaminant occurrence.